Idiopathic hallux saltans an unusual presentation of flexor hallucis longus tendinopathy: a case report - Mombello Zuleta, Franco; Redlich Cortés, Alex; Pellegrini Pucci, Manuel; Ortiz Mateluna, Cristian; Carcuro Urresti, Giovanni; Chaparro Ravazzano, Felipe (Journal of the Foot & Ankle, 2022)
Hallux saltans is a rare condition characterized by an entrapment of the flexor hallucis longus. Its tendon passes through the retromalleolar groove below the flexor retinaculum, directing the plantar aspect of the foot through a fibro-osseous tunnel below the sustentaculum tali. This study presents a young active patient without any of the conditions or etiological agents previously described in the literature that could explain the cause of this rare condition. After failing conservative treatments, an arthroscopic release of the tendon and the fibrous tunnel was performed, achieving direct visualization and minimal soft tissue injury. At six month follow-up, the patient resumed sports and daily living activities without symptoms. Level of Evidence V; Therapeutic Studies; Expert Opinion.